Government’s Implementation of Learning Strategies In Addressing Stunting - Sofia Azzahra; Iriani Ismail (Edumaspul: Jurnal Pendidikan, 2023)
The government has paid great attention to stunting prevention through Presidential Regulation No. 42 of 2013 concerning the National Movement for the Acceleration of Nutrition Improvement, which is now replaced by Presidential Regulation No. 72 of 2021 concerning the acceleration of stunting reduction, which aims to increase the government's commitment to improving nutrition, especially reducing stunting. The highest stunting rate in East Java is in Bangkalan Regency. The National Population and Family Planning Agency (BKKBN) stated that the stunting rate in Bangkalan District reached 38.9 percent. In Bangkalan Regency, Madura, in 2015, there were 240 toddlers who were malnourished, which increased by 36 toddlers from 2014 (Bangkalan Regency Health Office, 2015). This research aims to find out the government's strategy in tackling stunting and the work program carried out by the Arosbaya sub-district health center against stunting. The type of research used is descriptive qualitative. Using the case study method. This research data collection technique is using in-depth interviews, observation, documentation. By using the Purposive sampling type for sample determination which is done by determining the target of the population element that is thought to be most suitable for collecting data. Based on the latest data on Bangkalan Regency in October 2023, it was found that the number of cases of stunting toddlers in Arosbaya District was 38 cases. There is an innovative work program carried out by Puskesmas Arosbaya, namely the Puskesmas Care Staff program and Friday Barokah.